Maternal adverse childhood experiences and preschool children’s behavioral problems: exploring mediation via an adapted measure of adult attachment pattern - Kurbatfinski, Stefan; Dosani, Aliyah; Hayes, Andrew F.; Dewey, Deborah; Letourneau, Nicole (Frontiers in Psychology, 2025)
BackgroundMothers’ insecure adult attachment pattern (i.e., dismissive, preoccupied) has been proposed to positively mediate the associations between mothers’ adverse childhood experiences (ACEs) and their preschool children’s sex-specific behavioral problems. However, findings remain mixed with few focusing on a total score ranging from secure to insecure. Therefore, the aim of this study was to novelly employ the Revised-Experiences in Close Relationships (ECR-R) questionnaire to explore if (1) mothers’ adult attachment pattern measured continuously from secure to insecure mediates the relationship between maternal ACEs and children’s internalizing and externalizing behaviors and (2) child sex-assigned-at-birth moderated the effects.MethodsData (n = 636) derived from the prospective APrON Study (participants recruited during early pregnancy). Maternal ACEs were measured at child age 1, while children’s behavioral problems and mothers’ adult attachment pattern at child age 5.FindingsPositive, indirect effects on children’s internalizing (*bootstrap 95% CI [0.10, 0.58]) and externalizing (*[0.11, 0.62]) problems were supported. Post-hoc, a positive, indirect effect through preoccupied adult attachment pattern on their children’s internalizing problems was supported (*[0.04, 0.47]), but the effect did not differ from that of dismissive adult attachment pattern (*[−0.45, 0.15]). No moderation was observed (p > 0.05).SignificanceThis study is the first to employ the ECR-R to measure mothers’ adult attachment pattern continuously from secure to insecure. Findings suggest that (1) adult attachment pattern measured continuously mediates the association between mothers’ ACEs and their preschool children’s behavioral problems and (2) preoccupied adult attachment pattern behaviors may play a stronger role than those of dismissive.